Cost‐effectiveness of using Polyheal compared with surgery in the management of chronic wounds with exposed bones and/or tendons due to trauma in France, Germany and the UK - Guest, Julian F (Blackwell Publishing Ltd, 2013)

(untitled) (Int Wound J)
The objective of this study was to assess the cost‐effectiveness of Polyheal compared with surgery in treating chronic wounds with exposed bones and/or tendons (EB&T) due to trauma in France, Germany and the UK, from the perspective of the payers. Decision models were constructed depicting the management of chronic wounds with EB&T and spanned the period up to healing or up to 1 year. The models considered the decision by a plastic surgeon to treat these wounds with Polyheal or surgery and was used to estimate the relative cost‐effectiveness of Polyheal at 2010/2011 prices. Using Polyheal instead of surgery is expected to increase the probability of healing from 0·93 to 0·98 and lead to a total health‐care cost of €7984, €7517 and €8860 per patient in France, Germany and the UK, respectively. Management with surgery is expected to lead to a total health‐care cost of €12 300, €18 137 and €11 330 per patient in France, Germany and the UK, respectively. Hence, initial treatment with Polyheal instead of surgery is expected to lead to a 5% improvement in the probability of healing and a substantial decrease in health‐care costs of 35%, 59% and 22% in France, Germany and the UK, respectively. Within the models' limitations, Polyheal potentially affords the public health‐care system in France, Germany and the UK a cost‐effective treatment for chronic wounds with EB&T due to trauma, when compared with surgery. However, this will be dependent on Polyheal's healing rate in clinical practice when it becomes routinely available.